Comparison of Newly Diagnosed Ocular Hypertension and Open-Angle Glaucoma: Ocular Variables, Risk Factors, and Disease Severity - Yvonne M. Buys; Paul Harasymowycz; Rania Gaspo; Kenneth Kwok; Cindy M. L. Hutnik; Pierre Blondeau; Catherine M. Birt; Robert L. G. Piemontesi; Lisa F. Gould; Mark R. Lesk; Iqbal K. Ahmed (Journal of Ophthalmology)
Purpose. To describe the distribution of ocular variables, risk factors, and disease severity in newly diagnosed ocular hypertension (OH) or open-angle glaucoma (OAG). Methods. Eligible subjects underwent a complete history and examination. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) obtained from multiple logistic regression models were used to compare OAG to OH and advanced to early/moderate OAG. Results. 405 subjects were enrolled: 292 (72.1%) with OAG and 113 (27.9%) with OH. 51.7% had early, 27.1% moderate, and 20.9% advanced OAG. The OR for OAG versus OH was 8.19 (P<0.0001) for disc notch, 5.36 (P<0.0001) for abnormal visual field, 1.45 (P=0.001) for worsening mean deviation, 1.91 (P<0.0001) for increased cupping, 1.03 for increased age (P=0.030), and 0.36 (P=0.010) for smoking. Conclusions. Increased age was a risk for OAG, and smoking decreased the risk of OAG compared to OH. Almost half of the OAG subjects had moderate/advanced disease at diagnosis.